Discrete Event Simulation of Patient Admissions to a Neurovascular Unit. Issue 3 (5th September 2014) - Hahn-Goldberg, S.; Chow, E.; Appel, E.; Ko, F. T. F.; Tan, P.; Gavin, M. B.; Ng, T.; Abrams, H. B.; Casaubon, L. K.; Carter, M. W.
Abstract : Evidence exists that clinical outcomes improve for stroke patients admitted to specialized Stroke Units. The Toronto Western Hospital created a Neurovascular Unit (NVU) using beds from general internal medicine, Neurology and Neurosurgery to care for patients with stroke and acute neurovascular conditions. Using patient-level data for NVU-eligible patients, a discrete event simulation was created to study changes in patient flow and length of stay pre- and post-NVU implementation. Varying patient volumes and resources were tested to determine the ideal number of beds under various conditions. In the first year of operation, the NVU admitted 507 patients, over 66% of NVU-eligible patient volumes. With the introduction of the NVU, length of stay decreased by around 8%. Scenario testing showed that the current level of 20 beds is sufficient for accommodating the current demand and would continue to be sufficient with an increase in demand of up to 20%.